2005
DOI: 10.1002/jsfa.2405
|View full text |Cite
|
Sign up to set email alerts
|

Glycation of caseinate by fructose and fructo‐oligosaccharides during controlled heat treatment in the ‘dry’ state

Abstract: This paper investigates the controlled heating of caseinate with reducing sugars to produce glycoproteins with improved functionality for use in food. Caseinate was combined with inulin, fructose and a mixture of both inulin and fructose and the lyophilisates heated at a controlled water activity for up to 48 h. Caseinate-glucose and caseinate-lactose glycoconjugates were prepared for comparison. Conjugation between caseinate and fructose occurred readily at 60 • C and 67% relative humidity, modifying up to 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 30 publications
6
39
0
Order By: Relevance
“…11 As shown in Table 3, the corresponding increases in viscosity were 25-fold, 18-fold and 23-fold, respectively. These results, combined with the results above describing the effect of increasing fructose concentration, show that both the level of glycation and the type of sugar influence the protein viscosity.…”
Section: Effect Of Fructose Concentrationmentioning
confidence: 89%
See 3 more Smart Citations
“…11 As shown in Table 3, the corresponding increases in viscosity were 25-fold, 18-fold and 23-fold, respectively. These results, combined with the results above describing the effect of increasing fructose concentration, show that both the level of glycation and the type of sugar influence the protein viscosity.…”
Section: Effect Of Fructose Concentrationmentioning
confidence: 89%
“…All solutions of protein were lyophilised (−46 • C, 70-90 mtorr, 2-4 days) (Virtis Co. Freezemobile, Gardener, New York, USA) and subsequently preequilibrated to the desired relative humidity (RH) using desiccators containing saturated salt solutions of NaBr (50% RH); CuCl (67% RH) and BaCl (80% RH), as previously described by Oliver et al 11 The pre-equilibrated sample vials were capped, sealed and then heated at 60 • C for up to 120 h. Control experiments were carried out with caseinate without added reducing sugar.…”
Section: Glycoconjugate Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, glycation with dextran did not improve the rheological properties of caseinate, probably due to the limited extent of the reaction. Similarly, Oliver et al (2006) reported that glycated sodium caseinate with ribose, glucose, fructose, lactose, and inulin have increased viscosities compared to unmodified sodium caseinate with a non-Newtonian behavior. According to these authors, the main cause of increased viscosities was related to an increase of bound water to the glycated proteins.…”
Section: Reaction With Sugarsmentioning
confidence: 91%